Pulsed electromagnetic field modulates the inflammatory environment induced by interleukin-1β on human tendon-derived cells - Vinhas, A. (2018)
[Excerpt] Unresolved inflammatory processes in tendon healing have been related to the progression of tendinopathies. Thus, the management of tendon injuries may rely on cell-based strategies to identify and modulate tendon inflammatory cues. Pulsed electromagnetic field (PEMF) has been approved by FDA for orthopedics therapies and has been related to a reduction in pain and to improve healing. However, the influence of PEMF in tendon healing remains largely unknown. [...]